Children’s perspectives on disorder and violence in urban neighbourhoods - Carvalho, Maria João (Childhood, 2013)
UID/SOC/04647/2013Based on the analysis of 312 children’s neighbourhood drawings and narratives, this article discusses children’s socialization in six public housing neighbourhoods in Portugal, through children’s personal accounts of their lives. It then examines their perspectives on disorder and violence. Most complained about living in their neighbourhoods, referencing how social and spatial segregation, associated with a high exposure to violence, affect them. There is a ‘normalization’ of disorder and violence, due to its intense frequency, mainly in public spaces, which has an effect on children’s socialization, especially those to whom the street is ‘the’ central place in daily life.authorsversionpublishe